Adopting e-learning technology as a mode of instruction: How prepared are tertiary institutions in Cross River State, Nigeria? - Akuegwu, Basil Azubuike; Akeke, Mercy Nkiruka Godwin; Omorobi, Garieth Omorobi; Uchendu, Chika Christiana (Journal of Education and e-Learning Research, 2024)
This study investigates the level of preparedness among tertiary institutions for adopting e-learning as a mode of instruction in Cross River State, Nigeria. This study investigated institutional preparedness to adopt e-learning mode instruction based on the following indices: availability and accessibility of e-learning facilities, staff acquisition of e-learning skills, institutional provision for staff e-learning needs and institutional maintenance of e-learning facilities. This study adopted a descriptive survey research design and data was collected from 400 lecturers from the four tertiary institutions in Cross River State. The validated instrument was titled “Preparedness of Tertiary Institutions for E-Learning Technology Instruction Mode Questionnaire” (PTIETIMQ).” Descriptive statistics, percentages, mean and standard deviation) were used to answer the research questions while the population t-test of one sample mean was used to analyze the hypotheses. The results obtained from the analysis showed that some technologies required for implementing e-learning modes of instruction were mostly unavailable. However, the few available ones were inaccessible due to their disproportionate ratio to the student population and poor maintenance of the available e-learning facilities. Teaching staff proficiency in e-learning-related activities and institutional provision for their e-learning needs is significantly low suggesting that tertiary institutions are unprepared for e-learning modes of instruction. We recommend that institutional heads provide an enabling environment for e-learning technology to be embraced by teaching staff and students as a mode of instruction in line with global best practices.